VIABILITY AND ANTIMICROBIAL ACTIVITY OF STREPTOMYCES STRAINS FROM NCNM AFTER LYOPHILIZATION - Chiselita, Oleg; Burţeva, Svetlana; Bîrsa, Maxim; Bulimaga, Valentina; Vasiliciuc, Anastasia (CEP USM, 2016)
The article deals with the aspects related to lyophilization of streptomycetes strains, preserved in the National Collection of Nonpathogenic Microorganisms (NCNM). Was determined that lyophilization do not significantly modify the antimicrobial activity of streptomycetes. Maximum viability of strains of genus Streptomyces (83,2-90,2%) is ensured after lyophilization at initial titer by 9-11 log10UFC ml-1 in protective medium (gelatin 2,5% + glucose 7,5%) by rehydration with distillate water

Acest articol prezintă aspecte legate de liofilizarea tulpinilor de streptomicete, depozitate în Colecţia Naţională de Microorganisme Nepatogene (CNMN). A fost stabilit că liofilizarea nu modifică esenţial activitatea antimicrobiană a streptomicetelor. Viabilitatea maximă a tulpinilor genului Streptomyces (83,2-90,2%) este asigurată după liofilizarea la titrul iniţial 9-11 log10UFC ml-1 în mediu protectiv (gelatină 2,5% + glucosă 7,5%) şi la rehidratarea cu apă distilată.
VIABILITATEA ŞI ACTIVITATEA ANTIMICROBIANĂ A TULPINELOR DE STREPTOMYCES DIN CNMN DUPĂ LIOFILIZARE
Keywords: Streptomyces; lyophilization; viability; cryoprotectants; antimicrobial activity; activitate antimicrobiană; crioprotectori